Analisis Pendapatan Dan Kesejahteraan Usaha Tani Kembang Kol Di Kelurahan Banjar Sari Kecamatan Metro Utara - Ali, Karnila; Japlani, Ardiansyah; Alfandi, Ashari Mahendra (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to (1) determine the amount of income from the cauliflower village farm inBanjar Sari Village. (2) To determine the welfare level of cauliflower farming in Banjar SariVillage. This type of research is a type of quantitative research. Data were collected usingobservations and interviews conducted on 30 cauliflower farmers in Banjar Sari Village,Metro Utara District. Based on the results of the research that has been carried out, it isfound that the income of cauliflower farmers in Banjar Sari Village, Metro Utara District isquite high, the average income of cauliflower farmers from 30 respondents in one harvest isRp. 24,401,100, seen from the income of cauliflower farmers, the ratio value of allrespondents is R/C > 1, then all cauliflower farmers in Banjarsari Village (30 respondents)are included in the profitable category in doing farming. Based on the criteria of the worldbank (world bank) regarding the level of welfare, the welfare level of cauliflower farmers inBanjar Sari Village, Metro Utara District is quite high, as many as 24 farmers are includedin the prosperous category with a percentage of 80%, 3 farmers are included in the moderatecategory with a percentage 10% and the remaining 3 farmers are categorized as not yetprosperous with a percentage of 10% of the total 30 cauliflower farmers respondents inBanjarsari Village, Metro Utara District.